Republic of Kosovo : 2020 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Republic of Kosovo. (IMF Staff Country Reports; Country Report ;, 2021)
Kosovo has been hit hard by the COVID-19 pandemic. Despite policy support, economic activity is estimated to have fallen 6 percent in 2020 on account of the combined effect of strict domestic containment measures and international travel restrictions. The fiscal deficit increased to 7.7 percent of GDP, given the large fall in tax revenues and the implementation of mitigation and recovery measures of 4.2 percent of GDP. The current account deficit is estimated to have increased to 7.5 percent of GDP mainly due to a large decline in diaspora-related inflows, most notably in tourism. Gross international reserves declined but remain adequate in part due to the purchase under the IMF's Rapid Financing Instrument (RFI) in April 2020 and the use of other external financing. Banks have weathered the recession well to date, and the high pre-COVID19 liquidity levels and ample capital buffers bode well for the system's stability.